2018
DOI: 10.1155/2018/6204676
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma Treatment with Temozolomide and Bevacizumab and Overall Survival in a Rural Tertiary Healthcare Practice

Abstract: Background The efficacy of temozolomide (TMZ) chemotherapy for treating newly diagnosed glioblastoma (GBM), a primary brain tumor with short survival, was demonstrated in a clinical trial in 2005, and since then, the standard-of-care for newly diagnosed GBM has been maximal safe surgery followed by 60 Gray of radiation with concomitant and adjuvant TMZ (standard radiotherapy and TMZ). In 2009, clinical trials also reported on the efficacy of bevacizumab for treating recurrent GBM. We performed a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 35 publications
0
23
0
1
Order By: Relevance
“…VEGF staining is present in somatotroph adenomas, and we have not seen a difference between AIP mutation‒positive and AIP mutation‒negative cases (17). Both treatments were started with the hope of achieving additive or augmented effects, as data from patients with glioblastoma multiforme showed the combination of these two drugs causing remarkable tumor reduction along with survival benefits [(18) and ClinicalTrials.gov Identifier: NCT00612339, phase II, 2008]. Recently, temozolomide and bevacizumab treatment was stopped, as no further benefit was seen.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF staining is present in somatotroph adenomas, and we have not seen a difference between AIP mutation‒positive and AIP mutation‒negative cases (17). Both treatments were started with the hope of achieving additive or augmented effects, as data from patients with glioblastoma multiforme showed the combination of these two drugs causing remarkable tumor reduction along with survival benefits [(18) and ClinicalTrials.gov Identifier: NCT00612339, phase II, 2008]. Recently, temozolomide and bevacizumab treatment was stopped, as no further benefit was seen.…”
Section: Discussionmentioning
confidence: 99%
“…Having approved by the FDA in 2009, Bev has been employed either alone or in combination with TMZ in the treatment of both primary and recurrent GBM (Blumenthal et al, 2015). Preclinically, the antitumorigenic activity of Bev, in an intracranial GBM xenograft animal model derived from patient tumor spheroids showed a strong decrease in tumor growth, along with a significant reduction of vascular supply to the cells (Carter et al, 2018). The minimum steady‐state concentration of Bev was determined in a phase II clinical trial employing 69 patients, wherein 7.5 mg/kg every 3 weeks or 5 mg/kg every 2 weeks was found to be similar (Gaudreault et al, 2004).…”
Section: “Out‐of‐the‐box” Approaches For Gbm Treatmentmentioning
confidence: 99%
“…The median PFS rates in Post-Bev cohorts were found to be two months longer than that of Pre-Bev cohorts, indicating possible benefits of this drug in GBM treatment (Johnson et al, 2018). Another retrospective study was carried out, which reported that 307 patients with newly diagnosed GBM on treatment with TMZ and Bev have shown the increased progression of free survival rates of about 15.4 months (Carter et al, 2018). tumor suppressor gene (Janku et al, 2014).…”
Section: Vegf/vegfr Inhibitorsmentioning
confidence: 99%
“…The standard therapy relies on the Stupp protocol, officially proposed in 2005 [3,4]. The Stupp protocol is based on tumour surgical resection, followed by postoperative radiotherapy (RT), 60 Gy/30 fractions as standard, and concomitant plus adjuvant Temozolomide (TMZ) treatment [5]. Despite an increase in overall survival, the prognosis remains poor because of the development of GBM resistance to TMZ [6].…”
Section: Introductionmentioning
confidence: 99%